Low- pT e+e- Pair Production in Au +Au Collisions at sNN =200 GeV and U + U Collisions at sNN =193 GeV at STAR - STAR Collaboration (Physical Review Letters, 2018)
We report first measurements of e+e- pair production in the mass region 0.4<Mee<2.6 GeV/c2 at low transverse momentum (pT<0.15 GeV/c) in noncentral Au+Au collisions at sNN=200 GeV and U+U collisions at sNN=193 GeV. Significant enhancement factors, expressed as ratios of data over known hadronic contributions, are observed in the 40%-80% centrality of these collisions. The excess yields peak distinctly at low pT with a width (âpT2â ©) between 40 and 60 MeV/c. The absolute cross section of the excess depends weakly on centrality, while those from a theoretical model calculation incorporating an in-medium broadened ρ spectral function and radiation from a quark gluon plasma or hadronic cocktail contributions increase dramatically with an increasing number of participant nucleons. Model calculations of photon-photon interactions generated by the initial projectile and target nuclei describe the observed excess yields but fail to reproduce the pT2 distributions. © 2018 authors. Published by the American Physical Society. Published by the American Physical Society under the terms of the »https://creativecommons.org/licenses/by/4.0/» Creative Commons Attribution 4.0 International license. Further distribution of this work must maintain attribution to the author(s) and the published article's title, journal citation, and DOI. Funded by SCOAP3.
Keywords: Au+Au collisions; Colliding beam accelerators; Enhancement factor; Germanium compounds; Gold; Mass regions; Measurements of; Pair production; Photons; Transverse momenta; dept.phy; peer-reviewed